Study of demographic profile of animal bite cases and management practices in a dedicated anti rabies clinic of a tertiary care hospital, Hassan, Karnataka - Gowda, Praveen; K. J., Subhashini; Metri, Siddharam S.; Sundar, M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Animal bites cause a big burden in terms of morbidity and mortality throughout the world. These bites could be caused by rabid animals causing rabies. Annually about 59,000 persons die of rabies, of which 20,000 is from India alone. Rabies though 100% fatal is preventable with post-exposure prophylaxis which includes wound wash, anti-rabies vaccination (ARV) and rabies immunoglobulin. The objectives of the present study was to describe the demographic profile of animal bite cases and to assess the management practices of animal bite cases reporting to dedicated anti-rabies clinic (ARC) of a tertiary care hospital, Hassan, Karnataka. Methods: A cross-sectional study was conducted from the inception of anti-rabies clinic (12th October 2017) to August 2018 among animal bite cases reported to ARC. They were interviewed by using a semi-structured, pre-designed and pre-tested proforma. Data regarding socio-demographic profile were collected from the animal bite victims. All the animal bite cases were managed as per WHO guidelines. Results: The total number of animal bite victims reported to ARC during the study period was 3500. Majority of the bite victims belonged to adult population (20-60 years). Majority were males (66.2%). 77% belonged to the rural population. Dogs (97.1%) were the most common biting animal. 79% of the bites were provoked. Turmeric powder was the most commonly used irritant. Most bites belonged to Category III (84%). Category I, II, III bites were managed appropriately according to WHO guidelines. Conclusions: Knowing the burden, socio-demographic characteristics and the management of animal bite victims in the dedicated ARC of HIMS has helped the programme officer in implementing the National Rabies Control Programme in Hassan district.